2020
DOI: 10.1002/suco.202000247
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the flexural performance of GFRP repaired corroded reinforced concrete beams using passive acoustic emission technique

Abstract: The focus of the research is to evaluate the flexural behavior and performance of glass fiber reinforced polymer (GFRP) repaired reinforced concrete (RC) beams corroded to different levels using acoustic emission (AE) techniques. A significant improvement in the flexural characteristics of the GFRP repaired corroded beams is observed with a change in failure mode from brittle to ductile. The benefits of GFRP repair in corroded RC beams are further clearly demonstrated by AE monitoring parameters of cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…After the steel is corroded, the cross-section will be rusted, which will cause stress concentration in the weakest cross-section when the steel is stretched [5]. Scholars have established the relationship between the nominal yield augmentation f vyv of the corroded counterbearing and the rust loss rate η sv of the counterbearing section as [6]:…”
Section: Deterministic Model For Calculating the Shear Capacity Of Co...mentioning
confidence: 99%
“…After the steel is corroded, the cross-section will be rusted, which will cause stress concentration in the weakest cross-section when the steel is stretched [5]. Scholars have established the relationship between the nominal yield augmentation f vyv of the corroded counterbearing and the rust loss rate η sv of the counterbearing section as [6]:…”
Section: Deterministic Model For Calculating the Shear Capacity Of Co...mentioning
confidence: 99%
“…It is successfully demonstrated that combined AE and DIC monitoring enhance non-destructive monitoring skills in RC structures and effectively depict their cracking behavior. Garhwal et al (2021) investigated the flexural behavior of glass fiber reinforced polymer (GFRP) repaired reinforced beams. A novel methodology has been developed for assessing the performance of these beams using AE techniques.…”
Section: Introductionmentioning
confidence: 99%
“…GFRP‐reinforced RC columns have been given special attention among structural members as one of the main elements of concrete structures 1–4 . Many studies have been done to demonstrate the effect of using GFRP compared with steel on the axial behavior of RC columns 5–11 . De Luca and Nanni 12 presented a comprehensive overview of the behavior of concrete reinforced by GFRP bars.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Many studies have been done to demonstrate the effect of using GFRP compared with steel on the axial behavior of RC columns. [5][6][7][8][9][10][11] De Luca and Nanni 12 presented a comprehensive overview of the behavior of concrete reinforced by GFRP bars. A discussion of design approaches for RC structures with internal GFRP bars follows the introduction of the mechanical and durability properties of both concrete and GFRP bars.…”
Section: Introductionmentioning
confidence: 99%